Figurative Language Learning Challenges in EFL Short Stories - Dira Givanda; Deri Sis Nanda (English Education: Jurnal Tadris Bahasa Inggris, 2026)
The purpose of this study is to examine the difficulties students have when learning figurative language using short stories as real-world resources. The investigation was conducted at SMA Al-Azhar 3 Bandar Lampung and involved eleventh-grade students. Students' challenges in comprehending figurative phrases in short stories were investigated using a qualitative descriptive method. Data were collected through classroom observations, semi-structured interviews, and questionnaires. The results show that mastering figurative language presented a number of difficulties for the students. First, students' restricted vocabulary knowledge made it difficult for them to comprehend the meaning of figurative expressions. Second, students struggled to distinguish between personification, simile, and metaphor, among other forms of figurative language. Third, students found it challenging to interpret figurative meanings embedded in short stories. Students' understanding of literary texts was impacted by these difficulties. On the other hand, students were motivated to participate more actively in the learning process when short stories were used as real materials. To help students better comprehend figurative language in literary texts, teachers are advised to offer more contextual explanations and guided practice.